Chemical thinning programs for vigorous ‘Maxi Gala’ apple trees under black anti-hail netting in Southern Brazil - De Ross Marchioretto, Lucas; De Rossi, Andrea; Arduino Bettio Marodin, Gilmar (Revista Ceres, 2024)
Hail netting increases natural fruitlet drop. Mixing lower concentrations of Plant Growth Regulators (PGRs) and spraying on more advanced fruitlets could promote adequate crop load management and improve fruit quality. The objective of this study was to evaluate thinning programs with low concentrations of PGRs sprayed at advanced fruitlet size looking for reducing crop load, enhancing fruit quality, and preserving yield. On 2020/21 and 2021/22, in an orchard covered with hail netting in Bom Jesus-RS, eight programs were tested on vigorous ‘Maxi Gala’: Benzyladenine (BA)+Gibberellic acid4+7 (BA-GA) at full bloom (FB) and BA+Ethephon (ETH) at 15mm; BA-GA at FB and Naphthalene acetic acid+Carbaryl (CB) at 7 mm; BA-GA at FB and BA+CB at 15 mm; ETH+CB at 15 mm and Metamitron (MM)+ETH at 20 mm; BA-GA at FB and BA at 7 mm and MM at 20 mm; MM at 7 mm and MM at 20 mm; Manual Thinning Only; Untreated Control. The treatments containing CB reduced fruit set, although diminished yield unsustainably. All PGR programs improved fruit quality. In conclusion, BA-GA at FB and BA+ETH at 15 mm, and MM at 7 mm and MM at 20 mm reduce crop load, preserve yield and improve fruit quality.